2007
DOI: 10.1097/01.phh.0000296141.02295.16
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a Tobacco Quit Line Prior to and After a Tobacco Tax Increase

Abstract: Organizations supporting quit lines should anticipate an increase in the utilization of these services and changes in the characteristics of callers prior to and following an increase in tobacco taxes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
1
12
2
Order By: Relevance
“…This study's results are consistent with prior research showing that implementing an increase in excise taxes on tobacco will drive calls to the state tobacco control programs' free quitline services [3, 17]. Harwell et al reported an increase in call volumes to the Montana quitline following an increase in the state's cigarette taxes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study's results are consistent with prior research showing that implementing an increase in excise taxes on tobacco will drive calls to the state tobacco control programs' free quitline services [3, 17]. Harwell et al reported an increase in call volumes to the Montana quitline following an increase in the state's cigarette taxes.…”
Section: Discussionsupporting
confidence: 89%
“…Harwell et al reported an increase in call volumes to the Montana quitline following an increase in the state's cigarette taxes. They also reported that the tax attracted younger smokers to call the quitline, as well as more female and white smokers and heavier smokers [3]. In the current study, although smokers who called the quitline around the time of the federal tax increase were more likely to be white, no significant differences were found for gender or amount smoked.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Thus, quitlines have grown more with the development of the tobacco control movement and less with changes in the addiction counselling field 31. For example, quitlines may be promoted when a state announces a new secondhand smoke policy or tax increase 27 32. Quitlines often feature in anti-smoking media campaigns 33.…”
Section: Population Cessation: Interventions Consideredmentioning
confidence: 99%
“…Harwel et al in their study in the United States of America (USA) observed an increased number of calls to a smoking cessation phone line after the tax on cigarettes was raised and prices increased [21]. Willemsen et al in The Netherlands noted an increase in telephone contacts related to adding new European Union visual warnings on cigarette packets [22].…”
Section: Discussionmentioning
confidence: 99%